Evaluating the Integration of One Health in Surveillance Systems for Antimicrobial Use and Resistance: A Conceptual Framework - Aenishaenslin, Cécile; Häsler, Barbara; Ravel, André; Parmley, E. Jane; Mediouni, Sarah; Bennani, Houda; Stärk, Katharina D. C.; Buckeridge, David L. (Frontiers in Veterinary Science, 2021)
It is now widely acknowledged that antimicrobial resistance (AMR) surveillance must adopt a “One Health” (OH) approach to successfully address the significant threats this global public health issue poses to human, animal, and environmental health. While many protocols exist for surveillance evaluation, the specific aspect of integration of a OH approach in surveillance systems for antimicrobial usage (AMU) and AMR suffers from a lack of common and accepted guidelines and metrics for its monitoring and evaluation. This article presents a conceptual framework to evaluate OH integration in surveillance systems for AMR and AMU, named the Integrated Surveillance System Evaluation framework (ISSE framework). The ISSE framework aims to assist stakeholders and researchers designing an overall evaluation plan and to select relevant evaluation questions and tools. The framework was developed in partnership with the Canadian Integrated Program for Antimicrobial Resistance Surveillance (CIPARS). It consists of five evaluation components, which consider the system’s capacity to: 1) integrate a OH approach, 2) produce OH information and expertise, 3) generate actionable knowledge, 4) influence decision-making, 5) positively impact outcomes. For each component, a set of evaluation questions is defined, and links to other available evaluation tools are shown. The ISSE framework will help evaluators to assess systematically the different OH aspects of a surveillance system, to gain comprehensive information on the performance and value of these integrated efforts, and to use the evaluation results to refine and improve surveillance of AMR and AMU globally.